Study on Pretreatment of Saline Organic Wastewater by Ultrasound and Fenton Reagent - Lu, Jiaang; Xu, Ning; Chen, Jinfeng; Jiang, Weili; Han, Pingfang; Lu, Xiaoping (Asian Journal of Chemistry, 2011)
The Fenton method, unmodified and combined with ultrasound, was studied to treat saline organic wastewater. The effect of pH, Fe2+, H2O2, NaCl and Na2SO4 on degradation on reactive red dyestuff was explored. The pH value and Fe2+ concentration were key factors during the reactions. NaCl and Na2SO4 could decrease the degradation rate of reactive red dyestuff by the Fenton and ultrasound/Fenton method; NaCl could especially affect degradation via unmodified Fenton treatment. The degradation efficiency of active red dyestuff dropped to less than 4.01 % for the unmodified Fenton method in the presence of 100 ppm Na2SO4. The experiment proved that the ultrasound could not only improve the degradation efficiency of Fenton's reagent, but also weaken the negative effects of NaCl and Na2SO4. Reactive red dyestuff effluents were further treated by the US/Fenton method. A maximal degradation efficiency of reactive red dyestuff of 98.8 % was attained when the pH value was 3(± 0.2), the temperature was 20(± 2) ºC, the Fe2+ concentration was 13.2 mM, the H2O2 concentration was 264 mM, the reaction time was 4.5 h and the ultrasound frequency was 20 kHz. The effluent from chlorobutame manufacturing was degraded with US/Fenton treatment for 3 h after the coagulation process; its degradation efficiency of chemical oxygen demand achieved 94.5 %.